2023
DOI: 10.1021/acs.chemmater.3c00147
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in Low-Permittivity SrZrO3 Epitaxial Films

Abstract: Bulk SrZrO3 has an orthorhombic perovskite structure (Pbnm) with a central symmetry but exhibits a low dielectric constant. In this study, we reported a room-temperature ferroelectric SrZrO3 thin film with a low dielectric constant, induced by compressive strain from the SrTiO3 substrate. The presence of an out-of-phase boundary structure allows SrZrO3 with a large lattice mismatch to grow epitaxially on SrTiO3 substrates. The apparent atomic displacements in the lattice are revealed by scanning transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The origin of the OPB structure is then investigated. In the study of SrZrO 3 thin film, it has been observed that the appearance of the OPB structure is related to strain relaxation, suggesting that the OPB structure may be derived from lattice mismatch . A 7.5% lattice mismatch exists between bulk BZO and substrate STO, and the RSM results show that strain relaxation occurs in BZO thin films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of the OPB structure is then investigated. In the study of SrZrO 3 thin film, it has been observed that the appearance of the OPB structure is related to strain relaxation, suggesting that the OPB structure may be derived from lattice mismatch . A 7.5% lattice mismatch exists between bulk BZO and substrate STO, and the RSM results show that strain relaxation occurs in BZO thin films.…”
Section: Resultsmentioning
confidence: 99%
“…There are multiple mechanisms for the formation of OPB structure, with the use of steps or terraces on the substrate surface being one of the most common induction strategies. , Another approach for constructing OPB structures is to generate different phases or atom stack faults in thin films via nonstoichiometry. ,, The mismatch distortion caused by the large lattice mismatch between the film and substrate can also serve as the nucleation site for the OPB structure . Recently, we have observed the OPB structure in SrZrO 3 thin films . The emergence of the OPB structures is accompanied by the occurrence of strain relaxation, and as atoms are stacked, the OPB structure extends to the surface of the film, suggesting that the nucleation and expansion of the OPB structure have a significant relationship with the clamping effect of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario is also consistent with experimental observations . In addition, compressive epitaxial strains have been demonstrated to suppress antiferrodistortive-mode-associated ORRs and favor room-temperature ferroelectricity in CaTiO 3 -type paraelectrics, including tetragonal CaTiO 3 films (ε = −1.7% for LaSrAlO 4 substrates) and monoclinic SrZrO 3 films (ε = −5% for SrTiO 3 substrates) …”
Section: Exploration Of Emergent Ferroelectricsmentioning
confidence: 99%
“…Antiferromagnetic paramagnetic or nonmagnetic ground states are naturally predominant in most materials, and intricate interactions (e.g., the “ d 0 – d n ” dilemma of 3 d oxides) further hinder the integration of ferroelectricity and ferromagnetism into one system . To fully release the potential of these materials, strain engineering has been utilized to explore more unprecedented multiferroics, including EuTiO 3 , A MnO 3 (where A is an alkaline-earth metallic atom Ca, Sr, or Ba), SmMnO 3 , , and even paraelectric/nonmagnetic SrTiO 3 mediated by chemical, pressure, or local lattice strains. , The centrosymmetric cubic G-type antiferromagnetic structure of EuTiO 3 (a cubic lattice possessing a P m-3m space group and a T N of 5.5 K) impedes the emergence of coexisting magnetoelectrics, while in the TiO 6 coordination environment, the Ti 3 d 0 configuration and unpaired Eu 4 f 7 electrons ( S = 7/2), provide an avenue to simultaneously achieve ferroelectric and ferromagnetic ordering analogous to that in the type I BeFeO 3 multiferroic. Theoretical calculations have manifested that the 3-fold degeneracy of the TO 1 phonon mode is disrupted by a – b planar biaxial strains .…”
Section: Strain Engineering Beyond Ferroelectricitymentioning
confidence: 99%
“…Several materials have been proposed as alternatives to silica, including AlPO 4 –BPO 4 –SiO 2 ternaries, cordierite, and several borates. The characteristics of these compounds suggest that compounds with low atomic number atoms and open frameworks should be prioritized. Furthermore, the search for low-κ materials should be contrasted with efforts to find inorganic high-dielectric constant materials and ferroic materials where traditionally second-order Jahn–Teller ions such as Ti 4+ and lone-pair ions such as Bi 3+ are used . These works actually aid in the search for low-κ materials by suggesting which ions should be best avoided.…”
Section: Introductionmentioning
confidence: 99%